Analisis Isi Konten Youtube (Bloom Media) “Membahas Masalah Mental Health Generasi Strawberry” - Rhizqi Dwiputra Ramadhan; Arfian Suryasuciramdhan; Agil Hari; Firdy Ahmad Fariji; Refky Genta Saputra (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Gen-Z is a generation that is very spoiled by technology and the internet. The way they think and live their lives is different from previous generations. Generation Z is often referred to as the "Strawberry Generation", because they have a very soft mentality when experiencing life problems. Therefore, they are associated with the “strawberry generation” because they are like strawberries in that they break down very easily in stressful situations. To prevent the next generation from becoming the strawberry generation, parents should supervise their children, give them the freedom to study under supervision, and not spoil them too much when they are young. Once they grow up, their mentality will be formed.